P10.19.B An immunotoxin targeting CD317 for the treatment of glioblastoma. (5th September 2022) - Gramatzki, D; Weiss, T; Hänsch, L; Silginer, M; Rushing, E J; Roth, P; Gramatzki, M; Peipp, M; Weller, M
Abstract: Background: CD317 is an interferon-inducible cell surface receptor expressed in several solid cancer types. HM1.24-ETA' is a small immunotoxin with a CD317 single-chain variable fragment (svFv) antibody fused to a truncated version of Pseudomonas aeruginosa exotoxin A (ETA') that is explored as a novel therapeutic approach in CD317-expressing tumors. Material and Methods: CD317 mRNA expression in human gliomas and its association with survival was analyzed using the database of the Cancer Genome Atlas (TCGA). CD317 protein levels in human gliomas were assessed by immunohistochemistry. CD317 mRNA expression was assessed by RT-PCR and CD317 protein levels by flow cytometry in 13 human glioma cell lines in vitro . Efficacy of HM1.24-ETA' was analyzed in acute cytotoxicity assays in vitro . Finally, HM1.24-ETA' was evaluated in the intracranial human LN-229 glioma xenograft nude mouse model after intravenous injection. Results: Interrogation of the TCGA database showed that increased CD317 mRNA expression correlated with grade of malignancy among isocitrate dehydrogenase (IDH) wildtype and IDH-mutant gliomas. Enhanced CD317 mRNA expression was associated with inferior survival in glioblastoma and astrocytoma, IDH-mutant, WHO grade 4. Immunohistochemistry confirmed CD317 overexpression in human glioblastoma compared to lower grade astrocytomas. CD317 was expressed heterogeneously on mRNA and protein levels in glioma cell lines in vitro . HM1.24-ETA' induced acute cytotoxicity in CD317-positive glioma cells in vitro . CD317 expression and susceptibility to HM1.24-ETA'-induced cell death were enhanced by interferon-β. HM1.24-ETA' prolonged survival in the LN-229 xenograft nude mouse model. Conclusion: These data define CD317 as a novel target for treatment of human gliomas with immunoconjugates.